MENINGKATKAN HASIL BELAJAR IPS MENGGUNAKAN METODE BERMAIN PERAN MELALUI MODEL KOLABORATIF MATA ANGIN KELAS III SDN 010 UJUNGBATU T.P 2016/2017 - Fitra Yohana (STKIP Rokania Pasir Pangaraian, 2019)
The purpose of this study was to improve social studies learning outcomes with role playing methods in third grade students of SDN 010 Ujungbatu in the academic year 2016/2017. Observations on learning outcomes and observations of the learning process can be concluded that learning by applying the role playing method can improve social studies learning outcomes in class III Semester 1 010 Ujung Batu Public Elementary School 2016/2017 Academic Year. It is evident that the class average score on prasiklus is 63.23 with learning completeness of 39% in cycle 1 to 72.58 (74%) and in cycle 2 to 81.29 with 87% complete. Thus the hypothesis proposed by the researcher can be verified.